The development of the Arabic language curricula in public education in the Kingdom of Saudi Arabia - AL- HAZMI, Amani Suliman; Al- Aowaidi, Wafa Hafiz (Journal of Educational and Psychological Sciences, 2021)
The study aimed to identify the developments that took place in the Arabic language curricula in public education in the Kingdom of Saudi Arabia, which are the development of curriculum objectives, evaluation of Arabic language curricula, methods and techniques of education, strategies for teaching education and teacher preparation in general education. I took the historical approach as a research method, and I used the documents to discover the development of the Arabic language curricula. I explained the stages of development. They were presented in the form of simplified and clear tables, and I made some recommendations and proposals in the current study. Finally, I came to identify the developments that took place in the Arabic language curriculum in public education in the Kingdom of Saudi Arabia.